MENGENAL PENYELESAIAN SENGKETA KOMERSIAL INTERNASIONAL MELALUI ARBITRASE - santoso, edy (JURNAL ILMIAH LIVING LAW, 2015)
It is important to choice dispute resolution effectively in international trading. Arbitration is a form of alternative dispute resolution (ADR), is a legal technique for resolution of disputes outside the courts, wherein the parties to a dispute refer it to one or more persons, by whose decision they agree to be bound. In international trading, arbitration is most commonly used for the resolution of commercial disputes, particularly in the context of international commercial transactions. The role of arbitrate is as one of ADR system is very significant. It is to be ADR universal system in international contract. Arbitration can be either voluntary or mandatory and can be either binding or non-binding. It is depend on the parties with good faith. Win-win solution in dispute resolution to be main reason for those parties why choice arbitrates as ADR system.